A study of the effect of surfactant concentration of the stability of microbubbles using ultrasound imaging - Villanueva, Kathleen Kaye (2018)
This project presents a work towards designing of microbubbles formulation useful for contrast injection during diagnostic in vivo ultrasound examination. As the potential of microbubbles as ultrasound contrast agent has been phenomenally progressing as a result of its unique acoustic properties, optimizing the microbubbles to achieve long in vivo lifetime is crucial. Investigation of the shell material and gas composition of the microbubbles were performed to discern their impacts on the production and stability of the microbubbles. Polyoxyethylene glycol 40 (PEG40) stearate was used as a surfactant-stabilising shell. Presence of surfactant greatly influence the size and stability of the microbubbles and thus four different surfactant concentration of PEG40 (2, 5, 10 and 15%) along with increasing glycerol weight percentage were examined. Besides shell material, studying different gas composition was done as it also determines the echogenicity and stability of the microbubbles. Air and Nitrogen microbubbles were synthesized through high-shear rotor homogenizer and collected through three different needle sizes (23, 27 and 30 gauge) to examine their sensitivity to injection. Upon the synthesis of microbubbles from different formulations, analysis on its stability and acoustic testing of the microbubbles were executed. The results demonstrated that solution containing 10% PEG40 with 10% glycerol producing nitrogen microbubbles is the optimum composition of microbubbles capable for contrast injection to smaller artery and veins. It produced the most stable bubbles with the highest microbubble concentration, SNR of 68.73dB and a mean diameter of between 5µm and 6µm which contributes to improving accuracy and better imaging.